Observer performance methods for diagnostic imaging : foundations, modeling, and applications with r-based examples - Chakraborty, Dev P.; CRC Press (Boca Raton, FL : CRC Press, 2017)
"This book presents the technology evaluation methodology from the point of view of radiological physics and contrasts the purely physical evaluation of image quality with the determination of diagnostic outcome through the study of observer performance. The reader is taken through the arguments with concrete examples illustrated by code in R, an open source statistical language." ? from the Foreword by Prof. Harold L. Kundel, Department of Radiology, Perelman School of Medicine, University of Pennsylvania.
chapter 1 Preliminaries / Dev P. Chakraborty -- part A The receiver operating characteristic (ROC) paradigm -- chapter 2 The binary paradigm / Dev P. Chakraborty -- chapter 3 Modeling the binary task / Dev P. Chakraborty -- chapter 4 The ratings paradigm / Dev P. Chakraborty -- chapter 5 Empirical AUC / Dev P. Chakraborty -- chapter 6 Binormal model / Dev P. Chakraborty -- chapter 7 Sources of variability in AUC / Dev P. Chakraborty -- part B Two significance testing methods for the ROC paradigm -- chapter 8 Hypothesis testing / Dev P. Chakraborty -- chapter 9 Dorfman?Berbaum?Metz?Hillis (DBMH) analysis / Dev P. Chakraborty -- chapter 10 Obuchowski?Rockette?Hillis (ORH) analysis / Dev P. Chakraborty -- chapter 11 Sample size estimation / Dev P. Chakraborty -- part C The free-response ROC (FROC) paradigm -- chapter 12 The FROC paradigm / Dev P. Chakraborty -- chapter 13 Empirical operating characteristics possible with FROC data / Dev P. Chakraborty -- chapter 14 Computation and meanings of empirical FROC FOM-statistics and AUC measures / Dev P. Chakraborty -- chapter 15 Visual search paradigms / Dev P. Chakraborty -- chapter 16 The radiological search model (RSM) / Dev P. Chakraborty -- chapter 17 Predictions of the RSM / Dev P. Chakraborty -- chapter 18 Analyzing FROC data / Dev P. Chakraborty -- chapter 19 Fitting RSM to FROC/ROC data and key findings / Dev P. Chakraborty -- part D Selected advanced topics -- chapter 20 Proper ROC models / Dev P. Chakraborty -- chapter 21 The bivariate binormal model / Dev P. Chakraborty -- chapter 22 Evaluating standalone CAD versus radiologists / Dev P. Chakraborty -- chapter 23 Validating CAD analysis / Dev P. Chakraborty.
Keywords: Diagnostic imaging -- Data processing; Imaging systems in medicine; R (Computer program language); Receiver operating characteristic curves